An exploratory cross-cultural study: fathers' early involvement with infants. Issue 3 (17th February 2021) - Yeh, Chia Jung; Ballard, Sharon; Bian, Hui; Singh, Ajay; Chung, Chih-hung; Hwang, Shann Hwa; Moore, Lin; Samermit, Potchanat; Thongsaeng, Pimara
ABSTRACT: This research study recruited 107 fathers from the United States ( n = 31), Taiwan ( n = 36), and Thailand ( n = 37) to examine fathers' involvement in daily caregiving and engagement tasks, as well as fathers' accessibility to their infant(s) during weekdays and the weekend. Results indicated that the most influential demographic variables on father involvement were the interaction between fathers' education and income, number of children in the household, as well as country between the U.S. and Thailand regardless of living area, fathers' age, education and income alone. Additionally, fathers showed different involvement during weekdays and the weekend. Father's education level, number of children in the household, and the interaction between education and income had a combined effect on father involvement during the week and on the weekend. Fathers in the United States showed higher involvement in infant caregiving during the weekend when compared to fathers in Taiwan and Thailand.